Consumo alimentar e estado nutricional de crianças das comunidades quilombolas de Alagoas - Leite, Fernanda Maria de Banneux (2010)
To assess dietary intake and nutritional status of preschool children of quilombolas communities from Alagoas. By an across sectional study of children who were 13 to 59 months of 39 quilombolas communities from Alagoas. Dietary intake was assessed by recall of 24 hours. In analyzing of the data it was used the Dietary Reference Intakes (DRIs) as the recommendations proposed by the Institute of Medicine. To assess the nutritional status were used anthropometric indices of weight-for-age, height-for-age and weight-for-height, by adopting a cutoff of ± 2 standard deviations from the median of the standard WHO-2006 to characterize the condition of deficit or excessive. The diagnosis of anemia was made when the hemoglobin level was less than 11 g / dL. For this, it was used a drop of blood obtained by puncturing the finger for reading on portable portable Hemoglobin-meter (HemoCue). To better characterize the families, it was also collected socioeconomic and demographic data. Statistical analysis was performed with the aid packages Epi-info, version 3.5.1, and SPSS, version 16.0, using tests of parametric or nonparametric inference according to the characteristics of the variables obtained. It was studied 724 children (49.4% boys and 50.6% girls). The mean hemoglobin concentration was 11.0 ± 1.6 g / dL and the prevalence of anemia was 48.0%. The nutritional problem of greater significance was the low height-forage, affecting 9.7% of children, but 6.0% of preschool children were overweight or obese. The children presented a low-variety of food, characterized by the constant presence of Milk and cereal products, high intake of meat and low consumption of vegetables, tubers and roots. Based on the percentage of energy provided by carbohydrates, it was observed that a large proportion of the children surveyed, 85.9%, had adequate intake. However, regarding appropriateness of carbohydrate intake according to the EAR, 24.8% of preschool children showed a prevalence lower than recommended. The proportion of children who had a lipid intake below the lower limit of Acceptable Macronutrient Distribution Range – AMDR was high, 57.4%. Regarding consumption of energy from protein intake, most of the children was within the recommended limits of AMDR, as well as their suitability for the EAR for g /kg /day. According to the intake of micronutrients, there was a considerable prevalence of inadequacy for most vitamins and minerals, including zinc (17.0%), vitamins A (29.7%) and C (34.3%) and iron (20.2%). The analysis of dietary intake, according to economic class families (Classes B, C, D and E) revealed that children in the class E, the lower purchasing power, had lower average intake of those observed in other classes for most nutrients. The prevalence of malnutrition observed was similar to that prevailing for other children from Alagoas. The same was observed in relation to anemia, which often reached levels constituting a serious public health problem, a condition that can not be explained only by the inadequate intake of iron. The interaction with other nutritional deficiencies, coupled with the precarious conditions of environmental sanitation may explain another part of that determination. The results of this study support the hypothesis that belong to the less privileged economic class affects on the formation of habits and therefore the choice of food, reflecting on the nutritional status of children. It is recommend increased investment in infrastructure and public services in nutrition education, to contribute to the achievement of the human right to adequate food and a better standard of nutrition and health.